Генезис структур и предпосылки усовершенствования трансформаторов и реакторов преобразованием контуров электромагнитных систем (электродинамическая устойчивость и системы со стыковыми магнитопроводами) - Ставинский, А.А. (Електротехніка і електромеханіка, 2011)
Results and prospects of further evolution, features and ways of electrodynamic stability control for electromagnetic systems of transformers and reactors are analyzed. Examples of structural transformation of a spatial axial system with a belt-plate butt magnetic circuit on the basis of multiplane forming surfaces of rods and coil windows are presented.